Studies in philosophy for children : Harry sttotlemeier's discovery (Philadelphia : Temple University Press, 1992)
This book is about: Ethcal, Social, and Political issues; Logical issues; Pedagogical dimension; ...
Keywords: Philosophy; Lipman, Matthew; Harry Stottlemeier's discovery; Philosophy -- Study and teaching (Primary) -- United States; Lipman, Matthew -- Harry Stottlemeier's discovery; Children and philosophy